Serafino Zappacosta: An Enlightened Mentor and Educator - Carbone, Ennio; De Felice, Mario; Di Rosa, Francesca; D'Oro, Ugo; Fontana, Silvia; La Cava, Antonio; Maio, Michele; Matarese, Giuseppe; Racioppi, Luigi; Ruggiero, Giuseppina; Terrazzano, Giuseppe (Frontiers in Immunology, 2020)
With this article, the authors aim to honor the memory of Serafino Zappacosta, who had been their mentor during the early years of their career in science. The authors discuss how the combination of Serafino Zappacosta’s extraordinary commitment to teaching and passion for science created a fostering educational environment that led to the creation of the “Ruggero Ceppellini Advanced School of Immunology”. The review also illustrates how the research on the MHC and the inspirational scientific context in the Zappacosta laboratory influenced the authors’ early scientific interests, and subsequent professional work as immunologists.